QUALITY AND QUANTITY OF CLOSED HOUSE WASTE AS AN ALTERNATIVE FEED INGREDIENT (CASE STUDY - TEACHING FARM, FACULTY OF ANIMAL HUSBANDRY, UDAYANA UNIVERSITY) - Y. A. S., Sihite; Ariana, I N.T.; Putri, B.R.T (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
This study aims to determine the quality and quantity of closed house waste as an alternative ingridient of animal feed. The research was conducted in the closed house cage and 532 the Animal Nutrition and Food Laboratory of the Faculty of Animal Science, Udayana University from October to November 2021. The design used is a case study that investigates in depth the quality and quantity of closed house waste at the Faculty of Animal Science, Udayana University. The variables observed were the quality of dead and cull chicken waste, the quality of litter waste, the quantity of dead and cull chicken waste, and the quantity of litter waste. The results showed that chicken waste contained Dry Metter (DM), ash, Crude Protein (CP), Ether Extract (EE), Crude Fiber (CF), BETN, Gros Energi (GE) respectively; 96,17%, 7,89%, 56,98%, 29,72%, 0,14%, 1,44%, 6.360 kcal/kg while litter waste; 96,79%, 12,95%, 22,42%, 5,43%, 16,42%, 39,57%, 3.860 kcal/kg. The quantity of dead and cull chicken waste obtained an average of 1,85% per period and litter waste obtained as much as 1.150,1 kg per period. Based on the results of the study, it can be concluded that closed house waste has a quality and quantity that is feasible to be used as an alternative feed ingredient.